ARCTURUS laser: a versatile high-contrast, high-power multi-beam laser system. (2019) - Cerchez, M.; Prasad, R.; Aurand, B.; Giesecke, A. L.; Spickermann, S.; Brauckmann, S.; Aktan, E.; Swantusch, M.; Toncian, M.; Toncian, T.; Willi, O.
Abstract : With the latest configuration, the Ti:Sa laser system ARCTURUS (Düsseldorf University, Germany) operates with a double-chirped pulse amplification (CPA) architecture delivering pulses with an energy of 7 J before compression in each of the two high-power beams. By the implementation of a plasma mirror system, the intrinsic laser contrast is enhanced up to 10^-12 on a time scale of hundreds of picoseconds, before the main peak. The laser system has been used in various configurations for advanced experiments and different studies have been carried out employing the high-power laser beams as a single, high-intensity interaction beam ( I≈ 10^20 W/cm^2 ), in dual- and multi-beam configurations or in a pump–probe arrangement.